Nonaqueous electrolyte secondary battery and positive electrode using same

CN120418969APending Publication Date: 2025-08-01PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380087938.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-28
Filing Date
2023-12-15
Publication Date
2025-08-01

AI Technical Summary

Benefits of technology

[0016] According to the present disclosure, high safety and good battery performance can be achieved at the same time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120418969A_ABST
    Figure CN120418969A_ABST
Patent Text Reader

Abstract

A nonaqueous electrolyte secondary battery provided with a positive electrode, a negative electrode, a nonaqueous electrolyte, and a separator interposed between the positive electrode and the negative electrode, in which the positive electrode is provided with a positive electrode current collector and a positive electrode active material layer supported on the positive electrode current collector, and the positive electrode active material layer contains a positive electrode active material, a binder, and an additive. The additive is a polymer material having a melting point or thermal decomposition temperature of 200-500 DEG C inclusive, the polymer material is dispersed by forming a plurality of island-like regions in a cross-section of the positive electrode active material layer, and the variance value of the Wornoi pattern when the cross-section of the positive electrode active material layer is subjected to Wornoi division with respect to the island-like regions is 2 * 107 [mu] m 4 or less.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross - reference to related applications

[0002] This disclosure claims the benefit of the priority of Japanese Patent Application No. 2022 - 211731, filed with the Japan Patent Office on December 28, 2022, and the entire contents of the said patent application are incorporated herein by reference. Technical field

[0003] This disclosure relates to a non - aqueous electrolyte secondary battery and a positive electrode using the same. Background art

[0004] The higher the energy density of a secondary battery, the more important it is to improve safety. Among them, reducing heat generation caused by internal short - circuit is important. In the case of an internal short - circuit in the battery, even if the short - circuit part is minute, the separator melts due to Joule heat caused by the short - circuit current, forming a larger short - circuit part. When the short - circuit part expands and the short - circuit current increases, the battery temperature rises rapidly. The higher the energy density of the secondary battery, the more the Joule heat caused by the short - circuit current increases.

[0005] Patent Document 1 proposes a positive electrode active material, which is characterized in that in a composite oxide mainly composed of lithium and nickel having a layered crystal structure, it is a powder having an element composition represented by the general formula: Li a Ni 1-b-c M1 b M2 c O2, 0.95 ≤ a ≤ 1.05, 0.01 ≤ b ≤ 0.10, 0.10 ≤ c ≤ 0.20 (where M1 is one or more elements selected from Al, B, Y, Ce, Ti, Sn, V, Ta, Nb, W, Mo, and M2 is one or more elements selected from Co, Mn, Fe), and the conductivity σ of the compacted body when the powder is compression - molded to a density of 4.0 g / cm 3 at 25 °C is in the range of 5 × 10 -2 ≥ σ ≥ 5 × 10 -4 [S / cm].

[0006] Prior art documents

[0007] Patent documents

[0008] Patent Document 1: Japanese Unexamined Patent Application Publication No. 2000 - 315502 Summary of the invention

[0009] Problems to be solved by the invention

[0010] Patent Document 1 describes that according to the above - mentioned positive electrode active material, the thermal stability in the charged state is improved, and even in the case of an internal short - circuit in the battery, Joule heat generation caused by the short - circuit current can be suppressed, and safety can be easily ensured.

[0011] However, when controlling the conductivity as in Patent Document 1, the overall battery becomes a high resistance, resulting in a decrease in battery performance.

[0012] Solution to the problem

[0013] One aspect of the present disclosure relates to a non-aqueous electrolyte secondary battery including a positive electrode, a negative electrode, a non-aqueous electrolyte, and a separator interposed between the positive electrode and the negative electrode. The positive electrode includes a positive electrode current collector and a positive electrode active material layer loaded on the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material, a binder, and an additive. The additive is a polymer material having a melting point or thermal decomposition temperature of 200 °C or higher and 500 °C or lower. In a cross-section of the positive electrode active material layer, the polymer material forms a plurality of island-like regions and is dispersed, and the variance value of the Voronoi diagram when the cross-section of the positive electrode active material layer is subjected to Voronoi division with respect to the island-like regions is 2×10 7 μm 4 or less.

[0014] Another aspect of the present disclosure relates to a positive electrode for a secondary battery including a positive electrode current collector and a positive electrode active material layer loaded on the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material, a binder, and an additive. The additive is a polymer material having a melting point or thermal decomposition temperature of 200 °C or higher and 500 °C or lower. In a cross-section of the positive electrode active material layer, the polymer material forms a plurality of island-like regions and is dispersed, and the variance value of the Voronoi diagram when the cross-section of the positive electrode active material layer is subjected to Voronoi division with respect to the island-like regions is 2×10 7 μm 4 or less.

[0015] Effects of the invention

[0016] According to the present disclosure, high safety and good battery performance can be achieved at the same time.

[0017] The new features of the present invention are described in the claims, but the present invention relates to both the configuration and the content, and together with other objects and features of the present invention, can be better understood through the following detailed description with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is a longitudinal sectional view schematically showing the internal structure of a secondary battery according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0019] Hereinafter, examples will be given to illustrate the embodiments of the present disclosure, but the present disclosure is not limited to the examples described below. In the following description, specific numerical values and materials are sometimes exemplified, but other numerical values and materials can also be applied as long as the effects of the present disclosure can be obtained. In this specification, the description of "numerical value A to numerical value B" includes numerical value A and numerical value B, and can be replaced by "numerical value A or more and numerical value B or less". In the following description, when the lower limit and the upper limit of a numerical value related to a specific physical property, condition, etc. are exemplified, any one of the exemplified lower limits can be arbitrarily combined with any one of the exemplified upper limits as long as the lower limit is not more than the upper limit.

[0020] The non-aqueous electrolyte secondary battery includes: a lithium ion secondary battery that uses a material capable of reversibly absorbing and releasing lithium ions as a negative electrode active material, a lithium secondary battery in which lithium metal precipitates during negative electrode charging and lithium metal dissolves during discharging, a solid battery including a gel electrolyte or a solid electrolyte, and the like.

[0021] The non-aqueous electrolyte secondary battery related to the present disclosure includes a positive electrode, a negative electrode, and a non-aqueous electrolyte. A separator is usually disposed between the positive electrode and the negative electrode.

[0022] A. Positive Electrode

[0023] The positive electrode includes a positive electrode current collector and a positive electrode active material layer supported on the positive electrode current collector. The positive electrode active material layer is formed on the surface of the positive electrode current collector. Since the positive electrode active material layer is composed of a positive electrode mixture, it can also be called a positive electrode mixture layer.

[0024] [Positive Electrode Current Collector]

[0025] The positive electrode current collector is composed of a sheet-like conductive material. As the positive electrode current collector, a non-porous conductive substrate (such as a metal foil) or a porous conductive substrate (such as a mesh, a porous body, a punched sheet, etc.) is used.

[0026] [Positive Electrode Active Material Layer]

[0027] The positive electrode active material layer is supported on one or both surfaces of the positive electrode current collector. The positive electrode active material layer contains a positive electrode active material, a binder, and an additive, and may also contain a conductive aid. The additive is a polymer material having a melting point or a thermal decomposition temperature of 200°C or more and 500°C or less (hereinafter, the "melting point or thermal decomposition temperature" is sometimes collectively referred to as the "diffusion temperature").

[0028] The polymer material is dispersed by forming a plurality of island-like regions in the cross-section of the positive electrode active material layer. The island-like region is a dot-like region where the polymer material exists, and can also be said to be a granular region when observed macroscopically. The island-like region may be a region composed only of the polymer material (P), or an aggregated region formed by the aggregation of the polymer material (P) and materials other than the polymer material (P) (such as positive electrode active material, conductive assistant, etc.). The shape of the island-like region is not particularly limited and may be amorphous. The polymer material may be an insulating material or a mixture of an insulating material and a conductive material. Hereinafter, such a polymer material will also be referred to as "polymer material (P)".

[0029] The polymer material (P) has the effect of suppressing the increase in the positive electrode resistance at room temperature and increasing the positive electrode resistance at high temperature when an internal short circuit of the battery occurs. Therefore, high safety and good battery performance can be achieved at the same time.

[0030] Specifically, the polymer material (P) has the function of cutting off a part of the conduction path when an internal short circuit occurs, the short-circuit current increases, and the battery temperature rises. The polymer material (P) maintains an island shape at normal temperature and hardly increases the positive electrode resistance. On the other hand, when an internal short circuit occurs, the polymer material (P) melts before the battery temperature rises excessively. The molten polymer material (P) diffuses in the positive electrode active material layer. The polymer material (P) diffused into the positive electrode active material layer penetrates between the particles of the positive electrode active material, between the particles of the positive electrode active material and the conductive assistant, and between the particles of the conductive assistant, and partially blocks the conduction path.

[0031] In addition, if the polymer material (P) decomposes, the distance between the particles of the positive electrode active material increases, thereby increasing the positive electrode resistance. As a result, the short-circuit current is suppressed.

[0032] (Average area)

[0033] The average area of the island-like region can be 200 μm 2 Hereinafter. The average area of the island-like region is 200 μm 2 When the average area of the island-like region is 200 μm or less, the polymer material (P) has high dispersibility and can fully diffuse into a wide area of the positive electrode active material layer at high temperature, enabling a large increase in resistance. The average area of the island-like region can be 120 μm 2 or less, can be 60 μm 2 or less, can be 50 μm 2 or less, can be 30 μm 2 or less. The lower limit of the average area of the island-like region is not particularly limited, and can be, for example, 10 μm 2 or more.

[0034] Here, the average area of the island-shaped regions refers to the area obtained by dividing the total area St of the multiple island-shaped regions contained in the observation region of the cross-section of the positive electrode active material layer by the number N of the island-shaped regions contained in the observation region. Herein, the size of the observation region is set to a size where at least 30 or more island-shaped regions can be observed. The height of the observation region can be the same as the thickness (T) of the positive electrode active material layer, or can be 80% or more of the thickness. The length (W) of the observation region in the plane direction of the positive electrode active material layer can be 200 μm to 500 μm. In this case, the size of the observation region is T×W (μm 2 ).

[0035] (Average perimeter)

[0036] Next, the average perimeter of the island-shaped regions is preferably 60 μm or less. When the average perimeter of the island-shaped regions is 60 μm or less, it is considered that the sizes of the multiple island-shaped regions are sufficiently small. When the average perimeter is sufficiently small, the dispersibility of the polymer material (P) is sufficiently large, and at high temperatures caused by the occurrence of an internal short circuit, the polymer material (P) can diffuse into a wide region within the positive electrode active material layer. Therefore, the positive electrode resistance can be increased significantly. The average perimeter of the island-shaped regions can be 60 μm or less, can be 40 μm or less, can be 30 μm or less, and can be 20 μm or less. The lower limit of the average perimeter of the island-shaped regions is not particularly limited, and can be, for example, 1 μm or more.

[0037] Here, the average perimeter of the island-shaped regions refers to the length obtained by dividing the total length of the perimeters of the multiple island-shaped regions contained in the observation region of the cross-section of the positive electrode active material layer by the number of the island-shaped regions contained in the observation region. Herein, the size of the observation region is the same as the case of obtaining the average area of the island-shaped regions.

[0038] (Variance value of Voronoi diagram)

[0039] Next, the variance value (hereinafter, also referred to as "Voronoi variance value") of the Voronoi diagram (Voronoidiagram) when the observation region is subjected to Voronoi division for the island-shaped regions is 2×10 7 μm 4 or less. It can be said that the smaller the Voronoi variance value, the better the dispersibility. When the Voronoi variance value is 2×10 7 μm 4 or less, at high temperatures caused by the occurrence of an internal short circuit, the polymer material (P) can diffuse into a wide region within the positive electrode active material layer. Therefore, the positive electrode resistance can be increased significantly. The Voronoi variance value can be 2×10 6 μm 4 or less, can be 2×10 5 μm 4 or less, and can be 1×105 μm 4 Hereinafter, it may be 5×10 4 μm 4 or less. The lower limit of the Voronoi variance value is not particularly limited. For example, it may be 1×10 4 μm 4 or more.

[0040] The size of the observation region to be subjected to Voronoi division is the same as the case of obtaining the average area of the island regions. Specifically, Voronoi division is performed with the center (centroid) of all the island regions included in the observation region as the mother point, and the Voronoi variance value is calculated by calculating the histogram of the divided multiple regions. In addition, the Voronoi variance value is obtained as the average of three or more Voronoi variance values obtained in at least three observation regions.

[0041] (Aggregate particle area)

[0042] Next, in each island region in the positive electrode active material layer, the average area of the top 3 island regions with the largest area (hereinafter, also referred to as "aggregate particle area") is preferably 900 μm 2 or less. When the aggregate particle area of the island region is 900 μm 2 or less, it can be said that the dispersibility of the polymer material (P) is sufficiently large. Therefore, at high temperatures caused by the occurrence of internal short circuit, the polymer material (P) can diffuse into a wide area within the positive electrode active material layer, and can significantly increase the resistance. The aggregate particle area of the island region can be 800 μm 2 or less, can be 700 μm 2 or less, can be 400 μm 2 or less. The lower limit of the aggregate particle area of the island region is not particularly limited. For example, it may be 100 μm 2 or more. The top 3 island regions with the largest area are considered to be the aggregation regions of the polymer material (P) or the aggregation regions of the polymer material (P), the positive electrode active material, and the conductive assistant. By sufficiently reducing the area of such aggregation regions, the dispersibility of the polymer material (P) is significantly improved.

[0043] Here, the aggregate particle area of the island region is defined as the area obtained by dividing the total area of the island region with the largest area, the island region with the second largest area, and the island region with the third largest area among the multiple island regions included in the observation region of the cross section of the positive electrode active material layer by 3. The size of the observation region is the same as the case of obtaining the average area of the island region. Among them, the largest area of the island region is obtained as the average of three or more aggregate particle areas obtained in at least three different mutually parallel observation regions (cross sections).

[0044] The average area, average perimeter, variance value of the Voronoi diagram, aggregated particle area, etc. of the island-shaped region can be measured according to the following procedures.

[0045] (1) Preparation of the cross-section of the positive electrode active material layer

[0046] First, prepare the positive electrode to be measured. Next, cut the positive electrode active material layer and the positive electrode current collector simultaneously along the thickness direction of the positive electrode to form a cross-section. At this time, a thermosetting resin can be filled in the positive electrode active material layer and cured. For example, a cross-section specimen of the positive electrode active material layer can be obtained by the CP (Cross-Section Polisher) method, the FIB (Focused Ion Beam) method, etc.

[0047] The positive electrode to be measured is taken out from a secondary battery with a depth of discharge (DOD) of 90% or more. The depth of discharge (DOD) is the ratio of the discharged electric quantity to the electric quantity of the battery in the fully charged state. It should be noted that the charging electric quantity (i.e., the full charge amount) when charging a battery in the fully discharged state (DOD = 100%) to the fully charged state (SOC = 100%, DOD = 0%) is equivalent to the rated capacity. The voltage of the battery in the fully charged state corresponds to the charge termination voltage. The voltage of the battery in the fully discharged state corresponds to the discharge termination voltage.

[0048] (2) Photographing the cross-section of the positive electrode active material layer using a scanning electron microscope (SEM)

[0049] Next, observe the cross-section specimen of the positive electrode active material layer with an SEM. The observation using the SEM is performed, for example, at a magnification of 100 times to 500 times. The SEM image is taken in such a way that a region with a length of 200 μm or more (preferably 300 μm or more) can be observed in the plane direction of the positive electrode active material layer.

[0050] (3) Elemental analysis

[0051] Using SEM images of cross-sectional specimens, elemental analysis is performed using EDX (energy-dispersive X-ray spectroscopy) or EPMA (electron probe microanalyzer). By extracting components (such as sulfur elements) derived from the polymer material (P) from the analysis data of the cross-section, a mapping image of the polymer material (P) is obtained. By analyzing the mapping image using image analysis software, the average area, average perimeter, variance value of the Voronoi diagram, aggregated particle area, etc. of the island regions can be calculated. The mapping image can be obtained by binarizing the analysis data of the cross-section obtained by EDX or EPMA in such a way that the polymer material (P) is black and the area other than the polymer material (P) is white. For example, when performing EDX analysis in each of the 256×256 divided regions of the observation area, binarization is performed in such a way that components (such as sulfur elements) derived from the polymer material (P) are black and the other regions are white, thereby obtaining a mapping image. In the case where a set composed of two or more adjacent black regions in the longitudinal, lateral, or oblique direction is set as one island region, the length of the contour surrounding the set is the perimeter of the island region. In the case where a single black region is set as one island region, the length of the contour surrounding the single black region is the perimeter of the island region, and the area surrounded by each contour is the area of the island region.

[0052] Next, a method for obtaining the variance value of the Voronoi diagram is described.

[0053] First, Voronoi segmentation processing of the binary image is performed by image analysis software. In the Voronoi segmentation processing, the centers of each independent island region are extracted. For multiple centers, according to which center other points in the same distance space approach, they are divided into multiple regions (hereinafter, also referred to as "Voronoi regions"). The boundary of the Voronoi region corresponds to the locus of the bisectors of each center. Thereafter, the areas of each Voronoi region are extracted, and the variance value thereof is used as the Voronoi variance value. When the areas of each Voronoi region are Xi (i = 1, 2,..., n) and the average is Xave, the variance value V is obtained by the following formula.

[0054] V = 1 / n∑(Xi - Xave) 2

[0055] (4) Analysis conditions

[0056] Hereinafter, the preferred SEM-EPMA measurement conditions in the analysis of the cross-sectional specimen of the positive electrode active material layer are shown.

[0057] As a processing device, IB-19520CCP (cross-section polisher) manufactured by JEOL Ltd. can be used. The processing conditions are an acceleration voltage of 6 kV. The current value is 150 - 180 μA. The vacuum degree is set to 5×10 -4~2×10 -3 Pa.

[0058] The measuring device can use JSM-7900F (field emission scanning electron microscope) manufactured by JEOL Ltd. and XM-86030 (EPMA detector) manufactured by JEOL Ltd. During analysis, the acceleration voltage is 8 kV, and the SEM acceleration voltage is 2 kV. The electron beam current is 5×10 -8 A, and the observation magnification is set to 300 times. The measurement time is 30 ms.

[0059] Moreover, in the binarization process, regions with an X-ray intensity of 50 or more of the component (e.g., sulfur element) derived from the polymer material (P) detected under the above conditions can be set to black, and regions less than 50 can be set to white for binarization. It is also possible to set regions with an X-ray detection count of 50 cps or more and a signal / noise intensity ratio of 1.5 or more to black, and regions other than that to white for binarization.

[0060] [Polymer material (P)]

[0061] Hereinafter, exemplary polymer materials (P) will be described.

[0062] The melting point or thermal decomposition temperature (diffusion temperature) of the polymer material (P) is 200°C or higher and 500°C or lower. The positive electrode active material layer usually contains, in addition to the polymer material (P), a polymer material that functions as a binder. Among them, the binding property of the binder is higher than that of the polymer material (P). In addition, the binder may not form island-like regions. In other words, the positive electrode active material layer may contain a polymer material that forms island-like regions and a polymer material that does not form island-like regions. In addition, a polymer that does not melt or decompose at a diffusion temperature of 200°C or higher and 500°C or lower can usually be used as the binder. When the diffusion temperature of the polymer material (P) is lower than 200°C, the polymer material (P) may melt or decompose during normal battery use or manufacturing processes, resulting in deterioration of battery performance. In addition, when the diffusion temperature of the polymer material (P) exceeds 500°C, the diffusion rate of the polymer material (P) when the temperature rises decreases, so that a sufficient resistance increase effect cannot be obtained.

[0063] The polymer material (P) is preferably a linear polymer without a crosslinked structure. Since a linear polymer without a crosslinked structure has a large degree of freedom, it is easy to diffuse in the positive electrode active material layer at high temperatures and is easy to decompose. Therefore, the polymer material (P) easily penetrates between the particles of the positive electrode active material, between the particles of the positive electrode active material and the conductive additive, and between the particles of the conductive additive, and the conduction path is easily partially blocked.

[0064] (Average particle size (D50))

[0065] The polymer material (P) is in powder form before being mixed into the positive electrode mixture. The average particle diameter (D50) of the particles of the polymer material (P) constituting the powder is preferably 50 μm or less. By making the average particle diameter (D50) 50 μm or less, it is easy to control the above-mentioned average area, average perimeter, maximum area, Voronoi variance value, etc. within the desired numerical range. The average particle diameter (D50) is more preferably 40 μm or less, and still more preferably 30 μm or less. The lower limit of the average particle diameter (D50) is not particularly limited, and can be, for example, 1 μm or more.

[0066] Here, the average particle diameter (D50) of the polymer material (P) refers to the median particle diameter when the cumulative volume becomes 50% in the volume-based particle size distribution of the polymer material (P). The volume-based particle size distribution of the polymer material (P) can be measured, for example, by a laser diffraction scattering type particle size distribution measuring device. The sample of the polymer material (P) to be measured can be prepared by separating it from the positive electrode active material layer, and in the case where the raw material polymer material (P) before mixing with the positive electrode active material layer can be obtained, it can also be the raw material polymer material (P).

[0067] (BET specific surface area)

[0068] The BET specific surface area of the polymer material (P) is preferably 10 m 2 / g or less. The BET specific surface area is affected by the particle diameter of the polymer material (P), but the state of the particles themselves has a great influence. For example, when there are a large number of irregularities on the particle surface or the particles themselves are porous, the BET specific surface area becomes larger even if the average particle diameter (D50) is small. When the BET specific surface area is 10 m 2 / g or less, it is considered that there are few irregularities on the particle surface of the polymer material (P), or the particles themselves do not enclose a large amount of pores. In this case, it is speculated that the swelling stress acts strongly on the polymer material (P) during heating, and the diffusivity during heating is improved. The BET specific surface area can be 5 m 2 / g or less, can be 2 m 2 / g or less, can be 1.8 m 2 / g or less.

[0069] Here, the BET specific surface area of the polymer material (P) is measured by the gas adsorption method (BET one-point method). Nitrogen is used as the gas. The details of the BET method can follow JIS R1626. The sample of the polymer material (P) to be measured can be prepared by separating it from the positive electrode active material layer, and in the case where the raw material polymer material (P) before mixing with the positive electrode active material layer can be obtained, it can also be the raw material polymer material (P).

[0070] (Weight average molecular weight (Mw))

[0071] The weight-average molecular weight (Mw) of the polymeric material (P) preferably satisfies Mw < 50,000, more preferably satisfies 5,000 ≤ Mw < 50,000. By having the weight-average molecular weight (Mw) satisfy Mw < 50,000 (and thus 5,000 ≤ Mw < 50,000), the melting rate of the polymeric material (P) during heating becomes faster, the dispersibility is improved, and thermal decomposition becomes easier to proceed, so the effect of increasing the resistance of the positive electrode active material layer becomes greater. Mw is more preferably 30,000 or less, further preferably 20,000 or less, and may also be 15,000 or less.

[0072] The weight-average molecular weight (Mw) of the polymeric material (P) can be measured, for example, by ultra-high temperature gel permeation chromatography (GPC). Here, Mw is the weight-average molecular weight based on polystyrene.

[0073] The measurement conditions of the ultra-high temperature GPC are as follows. As the measurement device, ultra-high temperature GPC SSC-7110 can be used. As the column, 1 TSKguardcolumn HHR(S)HT and 2 TSKgel GMHHR-H(S)HT (7.8 mm I.D. * 30 cm) can be used. As the detector, a differential refractive index meter (RI detector) is used. As the pretreatment of the sample, weigh the sample of the polymeric material (P), add a specified amount of 1-chloronaphthalene (1-CN) as the solvent, and heat and dissolve it at 250 °C for 1 hour. Then, perform heat filtration using a PTFE filter with a pore size of 0.5 μm. As the sample injection volume, inject 500 μL of a solution with a sample concentration of 2 mg / mL. The flow rate is 1.0 mL / min, the measurement temperature is set to the column temperature of 210 °C, and the pre-oven temperature is set to 250 °C. Polystyrene is used as the molecular weight standard.

[0074] Regarding the obtained data (peaks), the low molecular weight side of the polymeric material (P) may partially overlap with the blank derived from the GPC eluent, but including this, the entire peak is analyzed to calculate the weight-average molecular weight.

[0075] (Specific examples of the polymeric material (P))

[0076] Hereinafter, preferred examples of the polymeric material (P) will be described.

[0077] In a polymer material (P), a polymer material (P) having a main chain containing a phenylene group and a thioether group (hereinafter, also referred to as "polymer material (PS)") has high chemical stability and is not easily combined with other materials. Therefore, it does not overly cover the particles of the positive electrode active material in the positive electrode active material layer, and it is easy to form island-like regions. In addition, when the polymer material (PS) melts above its melting point, the state change is large, and high diffusivity in the positive electrode active material layer can be exhibited. When using the polymer material (PS), in elemental analysis such as SEM-EDX and SEM-EPMA, a sulfur atom can be used as a component from the polymer material (P).

[0078] The main chain of the polymer material (PS) contains, for example, a repeating structure represented by the following formula (n is an arbitrary integer).

[0079]

[0080] n is usually 20 or more or 30 or more in the polymer. Such a simple structure has high chemical stability, and side reactions hardly occur in the positive electrode active material layer. In addition, the polymer material (PS) having the structure shown in the above formula is usually a linear polymer without a crosslinked structure, has a large degree of freedom when melted, and also has high diffusivity in the positive electrode active material layer after melting. It is considered that the polymer material (PS) with such a structure has high insulation and plays a great role in blocking the conduction paths when invading between the particles of the positive electrode active material, between the particles of the positive electrode active material and the conductive additive, and between the particles of the conductive additive.

[0081] As a more specific example of the polymer material (PS), polyphenylene sulfide (polyphenylene thioether) (hereinafter, also referred to as "PPS") can be cited.

[0082] The polymer material (P) may contain chloride ions in a mass ratio of 10 ppm or more and 1000 ppm or less, and further 10 ppm or more and 500 ppm or less. The amount of chloride ions contained in the polymer material (P) can be measured, for example, by peeling the positive electrode active material layer from the positive electrode, separating the polymer material (P) from the positive electrode active material layer, and analyzing by ion chromatography using ion-exchanged water as a solvent.

[0083] The polymer material (P) contained in the positive electrode active material layer can be in a small amount. The content rate of the polymer material contained in the positive electrode active material layer can be, for example, 0.01% by mass or more and 5% by mass or less, can be 0.1% by mass or more and 5% by mass or less, can be 0.3% by mass or more and 3% by mass or less, and can be 0.5% by mass or more and 2% by mass or less.

[0084] The polymer material (P) may be biased not on the positive electrode collector side of the positive electrode active material layer, but on the outermost surface side (i.e., the separator side). The internal short circuit of the battery often begins to expand on the separator side of the positive electrode active material layer. An internal short circuit occurs, for example, when a conductive foreign body penetrates the separator. By biasing the polymer material (P) on the separator side of the positive electrode active material layer, a high resistance region can be formed on the separator side of the positive electrode active material layer in the early stage after the short circuit occurs. Therefore, the expansion of the short circuit portion can be suppressed.

[0085] More specifically, when the thickness of the positive electrode active material layer is set to T, the existence probability Pb of the polymer material (P) existing in the area of the positive electrode active material layer from the surface of the positive electrode collector to 0.5T and the existence probability Pt of the polymer material (P) existing in the area of the positive electrode active material layer from the position 0.5T away from the surface of the positive electrode collector to the outermost surface (i.e., the surface on the separator side of the positive electrode active material layer) can satisfy, for example, 1<Pt / Pb, 1.2≤Pt / Pb, or 2≤Pt / Pb.

[0086] On the other hand, the polymer material (P) may be biased not to the outermost surface side (i.e., separator side) of the positive electrode active material layer, but to the positive electrode collector side. The short-circuit current of the battery tends to flow significantly on the positive electrode collector side of the positive electrode active material layer where the resistance is lowest. By biasing the polymer material (P) to the positive electrode collector side of the positive electrode active material layer, it is possible to selectively increase the resistance of the low-resistance region of the positive electrode active material layer. Therefore, the increase in short-circuit current can be suppressed.

[0087] More specifically, when the thickness of the positive electrode active material layer is set to T, the existence probability Pb of the polymer material (P) existing in the area of the positive electrode active material layer from the surface of the positive electrode collector to 0.5T and the existence probability Pt of the polymer material (P) existing in the area of the positive electrode active material layer from the position 0.5T away from the surface of the positive electrode collector to the outermost surface (i.e., the surface on the separator side of the positive electrode active material layer) can satisfy, for example, 1<Pb / Pt, 1.2≤Pb / Pt, or 2≤Pb / Pt.

[0088] Hereinafter, the region of the positive electrode active material layer from the surface of the positive electrode current collector to 0.5T is referred to as the "lower region", and the region of the positive electrode active material layer from the position 0.5T from the surface of the positive electrode current collector to the outermost surface is referred to as the "upper region".

[0089] It should be noted that when 1 < Pt / Pb is satisfied, the "observation region" can be set in the region as close to the center as possible in the thickness direction of the "upper region". On the other hand, when 1 < Pb / Pt is satisfied, the "observation region" can be set in the region as close to the center as possible in the thickness direction of the "lower region". In addition, when there is substantially no such bias in the distribution of the polymer material (P), the "observation region" can be set in the region as close to the center as possible at the center of the entire thickness T of the positive electrode active material layer (the point at a distance of 0.5T from the surface of the positive electrode current collector).

[0090] As described above, when the polymer material (P) is biased to one of the "lower region" and the "upper region", the content rate of the polymer material (P) contained in the other region can be made very small. In other words, with a small amount of the polymer material (P), the resistance of the positive electrode active material layer during heating can be efficiently increased, and the expansion of the short-circuited portion and the increase in the short-circuit current can be suppressed. Such a configuration is preferable in terms of easily maintaining the high capacity of the positive electrode.

[0091] Pb and Pt can be measured by analyzing the cross-sectional sample of the positive electrode obtained by the above method using SEM and EDX (or EPMA). Specifically, a mapping image of the polymer material (P) obtained from the analysis data of EDX of the cross-sectional sample is prepared. In the mapping images of the lower region and the upper region, the area occupied by the component (such as sulfur element) derived from the polymer material (P) is measured as the area of the polymer material (P). Moreover, the ratios of the area of the polymer material (P) to the areas of the lower region and the upper region are regarded as Pb and Pt, respectively. Pb and Pt can be measured in a rectangular observation region defined by the length of 300 μm in the plane direction of the positive electrode active material layer × the thickness T of the positive electrode active material layer. Pb and Pt can be the average values of Pb and Pt obtained in a plurality of (for example, three or more) observation regions, respectively.

[0092] The polymer material (P) can also be externally coated on the outermost surface side (i.e., the separator side) of the positive electrode active material layer to be biased. In this case, when the thickness of the positive electrode active material layer is set to T, the probability of existence Pb(q) of the polymer material (P) in the region of the positive electrode active material layer from the surface of the positive electrode current collector to 0.25T and the probability of existence Pt(q) of the polymer material (P) in the region of the positive electrode active material layer from the position at a distance of 0.75T from the surface of the positive electrode current collector to the outermost surface (i.e., the surface on the separator side of the positive electrode active material layer) can satisfy 5 ≤ Pt(q) / Pb(q) ≤  250.

[0093] <Manufacturing method of positive electrode>

[0094] Next, an example of a method for manufacturing a positive electrode according to an embodiment of the present disclosure will be described.

[0095] This manufacturing method includes the following steps: a step (I) of preparing a positive electrode paste containing a positive electrode active material, a binder, a conductive additive, a polymer material (P), and a dispersion medium; a step (II) of preparing a positive electrode current collector; a step (III) of coating the positive electrode current collector with the positive electrode paste to form a coating film; a step (IV) of drying the coating film to form an unrolled layer; and a step (V) of rolling the unrolled layer to form a positive electrode active material layer.

[0096] (I) Paste Preparation Step

[0097] The positive electrode paste is prepared by mixing a positive electrode mixture containing a positive electrode active material, a binder, a conductive additive, and a polymer material (P) with a liquid dispersion medium and dispersing it in the dispersion medium. The positive electrode mixture may further contain other components. As the liquid dispersion medium, an organic solvent having excellent affinity with the binder is used.

[0098] The average area, average perimeter, Voronoi variance value, maximum area, etc. of the island-shaped regions formed by the polymer material (P) can be controlled by the dispersion state of the polymer material (P) in the positive electrode paste. The polymer material (P) has a tendency to have significantly improved dispersibility by being premixed with the positive electrode active material in a dry state. However, the method for preparing the positive electrode paste is not particularly limited as long as the desired dispersion state of the polymer material (P) can be obtained. For example, the polymer material (P) may be premixed with the conductive additive in a wet state, and then the positive electrode active material may be added to the mixture and further mixed.

[0099] As the organic solvent, N-methyl-2-pyrrolidone (NMP) is preferably used, but alcohols such as ethanol, ethers such as tetrahydrofuran, amides such as dimethylformamide, and ketones such as cyclohexanone may also be used.

[0100] As the binder, fluororesin, hydrogenated nitrile rubber, etc. are preferably used, but there is no particular limitation as long as the adhesive force is high and it is stable in the positive electrode active material layer. Examples of the fluororesin include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), perfluoroalkoxy alkane (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), ethylene-tetrafluoroethylene copolymer (ETFE), vinylidene fluoride-hexafluoropropylene copolymer, etc. Among them, PVDF is preferred.

[0101] (II) Step of Preparing a Positive Electrode Current Collector

[0102] As the positive electrode current collector, a sheet-like conductive material (metal foil, mesh, porous body, punched sheet, etc.) is used. Among them, a metal foil is preferred. As the material of the positive electrode current collector, for example, stainless steel, aluminum, aluminum alloy, titanium, etc. can be exemplified. The thickness of the positive electrode current collector is not particularly limited, for example, it is 1 μm to 50 μm, and can be 5 μm to 30 μm.

[0103] (III) Step of forming a coating film of the positive electrode paste

[0104] A coating film is formed by coating the positive electrode paste on the surface of the positive electrode current collector. As the coating device for the positive electrode paste, for example, a bar coater, a gravure coater, a knife coater, a roll coater, a comma coater, a die coater, a lip coater, etc. are used. In the case where the polymer material (P) is biased to the lower region or the upper region of the positive electrode active material layer, a plurality of positive electrode pastes with different contents of the polymer material (P) can be prepared, and these pastes are repeatedly coated two or more layers to change the concentration of the polymer material (P) in the thickness direction.

[0105] (IV) Step of drying the coating film

[0106] Next, the coating film is dried to volatilize the dispersion medium, and an unrolled coating film is formed. For example, when the coating film is dried at a temperature of 150 °C or higher, and further 180 °C or higher, the polymer material (P) is likely to be in a state more biased toward the separator side than the positive electrode current collector side of the positive electrode active material layer.

[0107] (V) Step of rolling the unrolled layer

[0108] Next, the unrolled layer is rolled to form a positive electrode active material layer. The rolling conditions are not particularly limited. The density of the positive electrode active material in the positive electrode active material layer is, for example, 3.3 g / cm 3 or more and 4.0 g / cm 3 or less, and can be 3.5 g / cm 3 or more and 4.0 g / cm 3 or less.

[0109] B. Secondary battery

[0110] The non-aqueous electrolyte secondary battery of the embodiment of the present disclosure includes the above positive electrode, negative electrode, non-aqueous electrolyte, and a separator interposed between the positive electrode and the negative electrode. The non-aqueous electrolyte secondary battery can be a liquid secondary battery containing an electrolytic solution as an electrolyte, or a all-solid-state secondary battery containing a solid electrolyte as an electrolyte. Hereinafter, taking a lithium-ion secondary battery as an example, the configuration of the secondary battery will be specifically described.

[0111] [Positive electrode]

[0112] As the positive electrode, a positive electrode having the above-described characteristics is used. The positive electrode active material layer is composed of a positive electrode mixture. The positive electrode mixture contains a positive electrode active material, a binder, and a polymer material (P) as essential components, and may contain optional components. As the optional components, a conductive assistant, a thickener, etc. may be contained.

[0113] The thickness of the positive electrode active material layer is not particularly limited. For example, it may be 50 μm or more and 150 μm or less, or may be 75 μm or more and 125 μm or less. One positive electrode active material layer may also be formed of a plurality of layers having different morphologies from each other. For example, two or more layers containing positive electrode active materials having different average particle diameters may be laminated, or two or more layers having different types or compositions of positive electrode active materials may be laminated.

[0114] The average particle diameter (D50) of the particles of the positive electrode active material is, for example, 1 μm or more and 50 μm or less, and may be 5 μm or more and 25 μm or less. Here, the average particle diameter (D50) also refers to the median particle diameter at which the cumulative volume becomes 50% in the volume-based particle size distribution.

[0115] It should be noted that the average particle diameter of the positive electrode active material can be measured from the cross-sectional sample of the positive electrode active material layer described above. It is also possible to take an SEM image of the cross section in such a way that 10 or more positive electrode active material particles are observed, and by image processing, the diameters of the equivalent circles having the same area as the cross sections of 10 or more positive electrode active material particles are respectively obtained, and their average value is taken as the average particle diameter.

[0116] The positive electrode active material may contain a lithium-containing transition metal oxide. From the viewpoint of high capacity, the lithium-containing transition metal oxide preferably contains a lithium nickel oxide (composite oxide N), and the lithium nickel oxide (composite oxide N) contains lithium and Ni and has a layered rock salt-type crystal structure. The proportion of the composite oxide N in the positive electrode active material is, for example, 70% by mass or more, may be 90% by mass or more, or may be 95% by mass or more. The proportion of Ni contained in the composite oxide N among the metal elements other than Li may be 50 atomic% or more.

[0117] The composite oxide N is represented, for example, by the formula (1): Li α Ni<, x1 M1 x2 M2 (1-x1-x2) O 2+βrepresentation. Here, element M1 is at least one selected from the group consisting of V, Co, and Mn. Element M2 is at least one selected from the group consisting of Mg, Al, Ca, Ti, Cu, Zn, and Nb. Among them, in formula (1), 0.95 ≤ α ≤ 1.05, -0.05 ≤ β ≤ 0.05, 0.5 ≤ x1 < 1, 0 ≤ x2 ≤ 0.5, 0 < 1 - x1 - x2 ≤ 0.5. α increases or decreases during charge and discharge.

[0118] The composite oxide N may contain Ni, and contains at least one selected from the group consisting of Co, Mn, and Al as element M1 and element M2. Co, Mn, and Al contribute to the stabilization of the crystal structure of the composite oxide N.

[0119] From the viewpoints of cost reduction and high capacity, the proportion of Co contained in the composite oxide N among the metal elements other than Li is preferably 0 atomic % or more and 20 atomic % or less, more preferably 0 atomic % or more and 15 atomic % or less.

[0120] The proportion of Mn among the metal elements other than Li can be 10 atomic % or less, or can be 5 atomic % or less. The proportion of Mn among the metal elements other than Li can be 1 atomic % or more, or can be 3 atomic % or more, or can also be 5 atomic % or more.

[0121] The proportion of Al among the metal elements other than Li can be 10 atomic % or less, or can be 5 atomic % or less. The proportion of Al among the metal elements other than Li can be 1 atomic % or more, or can be 3 atomic % or more, or can also be 5 atomic % or more.

[0122] The composite oxide N can be represented, for example, by formula (2): Li α Ni (1-y1-y2-y3-z) Co y1 Mn y2 Al y3 M z O 2+β representation. Element M is an element other than Li, Ni, Co, Mn, Al, and oxygen, and can be at least one selected from the group consisting of Ti, Zr, Nb, Mo, W, Fe, Zn, B, Si, Mg, Ca, Sr, Sc, and Y. Among them, in formula (2), 0.95 ≤ α ≤ 1.05, -0.05 ≤ β ≤ 0.05, 0 ≤ y1 ≤ 0.1, 0 ≤ y2 ≤ 0.1, 0 ≤ y3 ≤ 0.1, 0 ≤ z ≤ 0.10. The atomic ratio of Ni, 1 - y1 - y2 - y3 - z (= v), is, for example, 0.8 or more, can be 0.85 or more, can be 0.90 or more, or can be 0.95 or more. In addition, v, which represents the atomic ratio of Ni, can be 0.98 or less, or can be 0.95 or less.

[0123] Examples of the conductive assistant that can be included as an optional component in the positive electrode active material layer include carbon nanotubes (CNT), carbon fibers other than CNT, and conductive particles (e.g., carbon black, graphite).

[0124] [Negative electrode]

[0125] The negative electrode includes at least a negative electrode current collector, for example, it includes a negative electrode current collector and a negative electrode active material layer. The negative electrode active material layer is loaded on one or both surfaces of the negative electrode current collector.

[0126] The negative electrode active material layer can be a negative electrode binder layer composed of a negative electrode binder. The negative electrode binder layer is in the form of a film or a thin sheet. The negative electrode binder contains particles of the negative electrode active material as an essential component and can contain a binder, a conductive assistant, a thickening agent, etc. as optional components. In addition, a lithium metal foil or a lithium alloy foil can also be attached to the negative electrode current collector as the negative electrode active material layer.

[0127] The negative electrode binder layer can be formed, for example, by coating a negative electrode slurry obtained by dispersing a negative electrode binder containing particles of the negative electrode active material, a binder, etc. in a dispersion medium on the surface of the negative electrode current collector and drying it. The dried coating film can be calendered as needed.

[0128] The negative electrode active material includes materials that electrochemically absorb and release lithium ions, lithium metal, lithium alloys, etc. As the materials that electrochemically absorb and release lithium ions, carbon materials, alloy-based materials, etc. are used. Examples of the carbon materials include graphite, easily graphitizable carbon (soft carbon), hardly graphitizable carbon (hard carbon), etc. Among them, graphite with excellent charge-discharge stability and less irreversible capacity is preferred. As the alloy-based materials, materials containing at least one metal capable of forming an alloy with lithium can be cited. Specifically, silicon, tin, silicon alloys, tin alloys, silicon compounds, etc. can be cited. Silicon oxide, tin oxide, etc. can be used, and other silicon-containing materials can also be used.

[0129] As the negative electrode current collector, a non-porous conductive substrate (metal foil, etc.), a porous conductive substrate (mesh, porous body, punched sheet, etc.) is used. Examples of the material of the negative electrode current collector include stainless steel, nickel, nickel alloy, copper, copper alloy, etc.

[0130] As the binder, styrene-butadiene rubber can be used, for example, but there is no particular limitation.

[0131] Examples of the conductive assistant include carbon nanotubes (CNT), carbon fibers other than CNT, and conductive particles (e.g., carbon black, graphite).

[0132] As a thickener, for example, carboxymethyl cellulose (CMC) and its modified products (including salts such as Na salts), cellulose derivatives such as methyl cellulose (cellulose ethers, etc.); saponified products of polymers having vinyl acetate units such as polyvinyl alcohol; polyethers (polyalkylene oxides such as polyethylene oxide, etc.) and the like can be cited.

[0133] [Separator]

[0134] The separator is interposed between the positive electrode and the negative electrode. The separator has a high ion permeability and has appropriate mechanical strength and insulation properties. As the separator, microporous films, woven fabrics, non-woven fabrics, etc. can be cited. For example, polyolefins such as polypropylene and polyethylene are used as the material of the separator.

[0135] The thickness of the separator can be, for example, 5 μm to 25 μm.

[0136] The separator may have a base material layer and a heat-resistant layer laminated on the base material layer. As the base material layer, microporous films, woven fabrics, non-woven fabrics, etc. can be used. The heat-resistant layer can be provided on at least one surface of the base material layer. The heat-resistant layer is preferably provided at least on the positive electrode side of the separator.

[0137] Here, the melting point or thermal decomposition temperature (diffusion temperature) of the polymer material (P) is preferably higher than the melting point of the base material layer. As the material of the base material layer, thermoplastic resins having a melting point are usually used. Among them, polyolefins such as polypropylene and polyethylene are preferably used. In the base material layer made of a thermoplastic resin, a shutdown function is usually provided. When the temperature reaches a high temperature exceeding a specified temperature, the pores of the base material layer are blocked. In other words, before the shutdown function takes effect, the current is allowed to flow through the battery, and sufficient performance as a power source is required. Assuming that the diffusion temperature of the polymer material (P) is lower than the melting point of the base material layer, the high resistance of the positive electrode active material layer caused by the polymer material (P) may develop, and sufficient performance as a power source may not be ensured.

[0138] The heat-resistant layer may contain an inorganic oxide filler as the main component (for example, 80% by mass or more of the heat-resistant layer), or may contain a heat-resistant resin as the main component (for example, 40% by mass or more of the heat-resistant layer). As the heat-resistant resin, polyamide resins such as aromatic polyamide (aramid), polyimide resins, polyamide-imide resins, etc. can be used.

[0139] The thickness of the base material layer can be, for example, 0% to 100% of the thickness of the separator, and can be, for example, 5 μm to 20 μm. When the thickness of the base material layer is 0% (no base material layer), a separator composed only of a heat-resistant layer can be used.

[0140] The thickness of the heat-resistant layer can be, for example, 0% to 100% of the thickness of the separator, and can be, for example, 0 μm to 15 μm.

[0141] [Non-aqueous electrolyte]

[0142] The non-aqueous electrolyte of a lithium-ion secondary battery has lithium-ion conductivity. The non-aqueous electrolyte can be a liquid electrolyte (electrolyte solution) or a solid electrolyte.

[0143] As the solid electrolyte, for example, a solid or gel polymer electrolyte, an inorganic solid electrolyte, etc. can be used. As the inorganic solid electrolyte, materials known in all-solid-state lithium-ion secondary batteries etc. (for example, oxide-based solid electrolytes, sulfide-based solid electrolytes, halogen-based solid electrolytes, etc.) can be used. The polymer electrolyte contains, for example, a lithium salt and a matrix polymer, or contains a non-aqueous solvent, a lithium salt, and a matrix polymer. As the matrix polymer, for example, a polymer material that gels by absorbing a non-aqueous solvent is used. As the polymer material, fluororesins, acrylic resins, polyether resins, etc. can be cited.

[0144] The electrolyte solution contains a non-aqueous solvent and an electrolyte salt. In the case of a lithium-ion secondary battery, the electrolyte salt contains at least a lithium salt. The concentration of the lithium salt in the electrolyte solution is, for example, 0.5 mol / L or more and 2 mol / L or less. The non-aqueous electrolyte solution can contain known additives.

[0145] As the non-aqueous solvent, for example, cyclic carbonates, chain carbonates, cyclic carboxylates, etc. can be used. As the cyclic carbonate, propylene carbonate (PC), ethylene carbonate (EC), etc. can be cited. As the chain carbonate, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), etc. can be cited. As the cyclic carboxylate, γ-butyrolactone (GBL), γ-valerolactone (GVL), etc. can be cited. The non-aqueous solvent can be used alone as 1 kind, or 2 or more kinds can be used in combination.

[0146] As the lithium salt, for example, lithium salts containing perchloric acid (LiClO4, LiAlCl4, LiB 10 Cl 10 etc.), lithium salts containing hydrofluoric acid (LiPF6, LiBF4, LiSbF6, LiAsF6, LiCF3SO3, LiCF3CO2, etc.), lithium salts containing fluorimide (LiN(SO2F)2, LiN(CF3SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(C2F5SO2)2, etc., lithium halides (LiCl, LiBr, LiI, etc.). The lithium salt can be used alone as 1 kind, or 2 or more kinds can be used in combination.

[0147] As an example of the structure of a secondary battery, a structure in which an electrode group formed by winding a positive electrode and a negative electrode with a separator therebetween is housed together with an electrolytic solution in an outer package can be cited. However, it is not limited thereto, and other types of electrode groups can also be applied. For example, it can also be a laminated electrode group in which a positive electrode and a negative electrode are laminated with a separator therebetween. The form of the secondary battery is not limited either, and for example, it can be a cylindrical type, a square type, a coin type, a button type, a laminated type, etc.

[0148] Hereinafter, with reference to Figure 1 the structure of the secondary battery will be described. Figure 1 FIG. 7 is a longitudinal sectional view of a cylindrical non-aqueous secondary battery 10 as an example of the present embodiment. However, the present disclosure is not limited to the following configuration.

[0149] The secondary battery 10 includes an electrode group 18, an electrolytic solution (not shown), and a bottomed cylindrical battery can 22 that houses them. A sealing body 11 is riveted and fixed to the opening of the battery can 22 with a gasket 21 interposed therebetween. Thus, the inside of the battery is sealed. The sealing body 11 includes a valve body 12, a metal plate 13, and an annular insulating member 14 interposed between the valve body 12 and the metal plate 13. The valve body 12 and the metal plate 13 are connected to each other at their respective central portions. A positive electrode lead 15a led out from the positive electrode plate 15 is connected to the metal plate 13. Therefore, the valve body 12 functions as an external terminal of the positive electrode. A negative electrode lead 16a led out from the negative electrode plate 16 is connected to the inner surface of the bottom of the battery can 22. An annular groove portion 22a is formed near the open end of the battery can 22. A first insulating plate 23 is disposed between one end face of the electrode group 18 and the annular groove portion 22a. A second insulating plate 24 is disposed between the other end face of the electrode group 18 and the bottom of the battery can 22. The electrode group 18 is formed by winding a positive electrode plate 15 and a negative electrode plate 16 with a separator 17 therebetween.

[0150] (Supplementary Note)

[0151] The following technology is disclosed by the above description.

[0152] (Technology 1)

[0153] A non-aqueous electrolyte secondary battery, which includes a positive electrode, a negative electrode, a non-aqueous electrolyte, and a separator interposed between the positive electrode and the negative electrode,

[0154] the positive electrode includes a positive electrode current collector and a positive electrode active material layer loaded on the positive electrode current collector,

[0155] the positive electrode active material layer includes a positive electrode active material, a binder, and an additive,

[0156] the additive is a polymer material having a melting point or thermal decomposition temperature of 200°C or higher and 500°C or lower,

[0157] In the cross-section of the positive electrode active material layer, the polymer material is dispersed by forming a plurality of island-like regions.

[0158] The variance value of the Voronoi diagram when the cross-section of the positive electrode active material layer is subjected to Voronoi division for the island-like regions is 2×10 7 μm 4 or less.

[0159] (Technology 2)

[0160] The non-aqueous electrolyte secondary battery according to Technology 1, wherein the average perimeter of the island-like regions is 60 μm or less.

[0161] (Technology 3)

[0162] The non-aqueous electrolyte secondary battery according to Technology 1 or 2, wherein the average area of the island-like regions is 200 μm 2 or less.

[0163] (Technology 4)

[0164] The non-aqueous electrolyte secondary battery according to any one of Technologies 1 to 3, wherein the average area of the top 3 island-like regions with the largest area is 900 μm 2 or less.

[0165] (Technology 5)

[0166] The non-aqueous electrolyte secondary battery according to any one of Technologies 1 to 4, wherein the average particle diameter of the polymer material is 50 μm or less.

[0167] (Technology 6)

[0168] The non-aqueous electrolyte secondary battery according to any one of Technologies 1 to 5, wherein the BET specific surface area of the polymer material is 10 m 2 / g or less.

[0169] (Technology 7)

[0170] The non-aqueous electrolyte secondary battery according to any one of Technologies 1 to 6, wherein the weight average molecular weight (Mw) of the polymer material satisfies Mw ≤ 50000.

[0171] (Technology 8)

[0172] The non-aqueous electrolyte secondary battery according to any one of Technologies 1 to 7, wherein the polymer material has a main chain containing a phenylene group and a sulfide group.

[0173] (Technology 9)

[0174] The non-aqueous electrolyte secondary battery according to any one of Technologies 1 to 8, wherein the main chain contains a repeating structure represented by the following formula (n is an arbitrary integer).

[0175]

[0176] (Technology 10)

[0177] The non-aqueous electrolyte secondary battery according to any one of Technologies 1 to 9, wherein the polymer material contains polyphenylene sulfide (polyphenylene sulfide).

[0178] (Technology 11)

[0179] The non-aqueous electrolyte secondary battery according to any one of Technologies 1 to 10, wherein the polymer material contains chloride ions in a mass ratio of 10 ppm or more and 1000 ppm or less.

[0180] (Technology 12)

[0181] The non-aqueous electrolyte secondary battery according to any one of Technologies 1 to 11, wherein the content rate of the polymer material contained in the positive electrode active material layer is 0.01% by mass or more and 5% by mass or less.

[0182] (Technology 13)

[0183] The non-aqueous electrolyte secondary battery according to any one of Technologies 1 to 12, wherein when the thickness of the positive electrode active material layer is set to T, the presence probability Pb of the polymer material existing in the region of the positive electrode active material layer from the surface of the positive electrode current collector to 0.5T and the presence probability Pt of the polymer material existing in the region of the positive electrode active material layer from the position 0.5T away from the surface of the positive electrode current collector to the outermost surface satisfy 1 < Pt / Pb.

[0184] (Technology 14)

[0185] The non-aqueous electrolyte secondary battery according to any one of Technologies 1 to 13, wherein when the thickness of the positive electrode active material layer is set to T, the presence probability Pb of the polymer material existing in the region of the positive electrode active material layer from the surface of the positive electrode current collector to 0.5T and the presence probability Pt of the polymer material existing in the region of the positive electrode active material layer from the position 0.5T away from the surface of the positive electrode current collector to the outermost surface satisfy 1 < Pb / Pt.

[0186] (Technology 15)

[0187] The non-aqueous electrolyte secondary battery according to any one of Technologies 1 to 14, wherein the separator has a base material layer and a heat-resistant layer laminated on the base material layer.

[0188] The melting point or thermal decomposition temperature of the polymer material is not less than the melting point of the base material layer.

[0189] (Technology 16)

[0190] The non-aqueous electrolyte secondary battery according to any one of Technologies 1 to 15, wherein the positive electrode active material contains a lithium-containing transition metal oxide.

[0191] The lithium-containing transition metal oxide contains lithium nickel oxide, and the lithium nickel oxide contains lithium and Ni and has a layered rock salt-type crystal structure.

[0192] The proportion of Ni contained in the lithium nickel oxide among the metal elements other than Li is 50 atomic% or more.

[0193] (Technology 17)

[0194] The non-aqueous electrolyte secondary battery according to any one of Technologies 1 to 16, wherein the lithium nickel oxide is represented by the formula: Li α Ni x1 M1 x2 M2 (1-x1-x2) O 2+β wherein

[0195] Element M1 is at least one selected from the group consisting of V, Co, and Mn.

[0196] Element M2 is at least one selected from the group consisting of Mg, Al, Ca, Ti, Cu, Zn, and Nb, and satisfies:

[0197] 0.95 ≤ α ≤ 1.05,

[0198] -0.05 ≤ β ≤ 0.05,

[0199] 0.5 ≤ x1 < 1,

[0200] 0 ≤ x2 ≤ 0.5,

[0201] 0 < 1 - x1 - x2 ≤ 0.5.

[0202] (Technology 18)

[0203] The non-aqueous electrolyte secondary battery according to any one of Technologies 1 to 17, wherein the binder contains at least one selected from the group consisting of fluororesin and hydrogenated nitrile rubber.

[0204] (Technology 19)

[0205] A positive electrode for a secondary battery, wherein,

[0206] the positive electrode active material layer contains a positive electrode active material, a binder, and an additive,

[0207] the additive is a polymer material having a melting point or thermal decomposition temperature of 200 °C or higher and 500 °C or lower,

[0208] in the cross-section of the positive electrode active material layer, the polymer material is dispersed to form a plurality of island-like regions,

[0209] the variance value of the Voronoi diagram when the cross-section of the positive electrode active material layer is subjected to Voronoi division for the island-like regions is 2×10 7 μm 4 or less.

[0210] Hereinafter, the present disclosure will be specifically described with reference to samples of experimental examples, but the present disclosure is not limited to the following embodiments.

[0211] "Sample A1"

[0212] [Fabrication of Positive Electrode]

[0213] As the positive electrode active material, a composite oxide N(LiNi 0.85 Co 0.10 Al 0.05 O2) with an average particle diameter of 13 μm was used. In addition, as the positive electrode current collector, an aluminum foil with a thickness of 15 μm was prepared.

[0214] A positive electrode mixture containing a positive electrode active material, acetylene black, and polyvinylidene fluoride (PVDF) in a mass ratio of 95:2.5:2.5 and containing polyphenylene sulfide (PPS) (average particle diameter (D50) = 10 μm, weight average molecular weight 28000, BET specific surface area 1.1 m 2 / g, melting point 280 °C, chloride ion content 50 ppm) at a content rate of 1.3 mass% was added with NMP and stirred to prepare a positive electrode slurry.

[0215] The positive electrode slurry was coated on the surface of the aluminum foil serving as the positive electrode current collector, and the coating film was dried to form an unrolled layer on both sides of the aluminum foil. At this time, the drying temperature was controlled to 50 °C so that the distribution of PPS in the positive electrode active material layer was not biased toward the lower layer region or the upper layer region, and it was left to dry.

[0216] Next, the unrolled layer was rolled to form a positive electrode active material layer having a density of 3.6 g / cm 3 The overall thickness of the rolled positive electrode was 160 μm.

[0217] The average area of the island regions formed from the polymeric material (P) obtained using the above method is 11 μm 2 .

[0218] [Fabrication of the negative electrode]

[0219] Water was added to a negative electrode mixture containing graphite as a negative electrode active material, sodium carboxymethyl cellulose (CMC-Na), and styrene-butadiene rubber (SBR) in a mass ratio of 96:2:2, and the mixture was stirred to prepare a negative electrode paste. Subsequently, the negative electrode paste was coated on the surface of a copper foil serving as a negative electrode current collector, and after drying the coating film, rolling was performed to form a negative electrode active material layer on both sides of the copper foil. The density of the negative electrode active material in the negative electrode active material layer was adjusted to 1.6 g / cm 3 . The overall thickness of the negative electrode was 170 μm

[0220] [Fabrication of the non-aqueous electrolyte]

[0221] A non-aqueous electrolyte was prepared by dissolving LiPF6 at a concentration of 1.0 mol / L in a mixed solvent containing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 3:7

[0222] [Fabrication of the secondary battery]

[0223] Tabs were respectively attached to each electrode, and the positive electrode and the negative electrode were wound in a spiral shape with the tabs located at the outermost peripheral portion, with a separator (thickness 14 μm) therebetween, thereby fabricating an electrode assembly. The separator had a base layer of a microporous film made of polyethylene with a thickness of 10 μm and a heat-resistant layer with a thickness of 4 μm laminated on one side (positive electrode side) of the base layer. The melting point of the microporous film was 150 °C. The heat-resistant layer contained 20 mass% of an inorganic oxide filler (aluminum oxide), and the remaining portion was composed of aromatic polyamide. The electrode assembly was inserted into an outer package made of an aluminum laminated film, vacuum-dried at 105 °C for 2 hours, then the electrolyte was injected, and the opening of the outer package was sealed to obtain a sample A1 of the secondary battery

[0224] 《Sample B1》

[0225] A sample B1 of the secondary battery was fabricated in the same manner as sample A1, except that the positive electrode mixture did not contain the polymeric material (P)

[0226] 《Samples A2 - A4, B2》

[0227] Samples A2 - A4 and B2 of the secondary battery were fabricated in the same manner as sample A1, except that the content ratio of the polymeric material (P) contained in the positive electrode mixture and the stirring conditions during the preparation of the positive electrode paste were changed so that the average area of the island regions changed as shown in Table 1

[0228] [Evaluation]

[0229] The obtained samples were evaluated as follows.

[0230] (a) In an environment at 25°C, the battery samples were charged at a constant current of 0.3It until the voltage reached 4.2V, and then charged at a constant voltage of 4.2V until the current reached 0.05It.

[0231] (b) In an environment at 25°C, the tip of a round nail (diameter 2.7 mm) was brought into contact with the central part of the battery sample charged in (a), and the nail was punctured at a speed of 1 mm / second. After detecting a voltage drop (Δ50 mV) of the battery caused by an internal short circuit, the puncture of the round nail was immediately stopped. The surface temperature of the battery was measured 1 minute after the sample short-circuited. The surface temperatures of samples A1 - A4 and samples B1, B2 are shown in Table 1.

[0232] [Table 1]

[0233]

[0234] According to Table 1, compared with samples B1 and B2, the surface temperatures of samples A1 - A4 were significantly reduced. Thus, it can be seen that the safety when an internal short circuit of the battery occurs can be improved with little influence on the battery capacity.

[0235] 《Samples R1a - R4a, Sample CRa》

[0236] By appropriately changing the content ratio of the polymer material (P) contained in the positive electrode mixture and the stirring conditions during the preparation of the positive electrode paste, the average perimeter of the island regions was changed as shown in Table 2. Other than that, samples R1a - R4a and CRa of secondary batteries were made in the same way as sample A1 and evaluated in the same way.

[0237] [Table 2]

[0238]

[0239] In Table 2, compared with samples B1 and B2, the surface temperatures of samples R1a - R4a were significantly reduced, and compared with samples A3 and A4, the surface temperatures were reduced. Thus, it can be seen that the safety when an internal short circuit of the battery occurs can be further improved with little influence on the battery capacity.

[0240] 《Samples R1b - R4b, Sample CRb》

[0241] By appropriately changing the content ratio of the polymer material (P) contained in the positive electrode mixture and the stirring conditions during the preparation of the positive electrode slurry, the Voronoi variance value of the island-shaped region is changed as shown in Table 3. Except for this, samples R1b to R4b and CRb of the secondary battery are produced in the same manner as sample A1, and the evaluation is carried out in the same way.

[0242] [Table 3]

[0243]

[0244] As can be seen from Table 3, compared with samples B1 and B2, the surface temperatures of samples R1b to R4b are significantly reduced, and the safety when the internal short circuit of the battery occurs can be further improved with little influence on the battery capacity.

[0245] 《Samples R1c to R4c, Sample CRc》

[0246] By appropriately changing the content ratio of the polymer material (P) contained in the positive electrode mixture and the stirring conditions during the preparation of the positive electrode slurry, the aggregated particle area of the island-shaped region is changed as shown in Table 4. Except for this, samples R1c to R4c and CRc of the secondary battery are produced in the same manner as sample A1, and the evaluation is carried out in the same way.

[0247] [Table 4]

[0248]

[0249] As can be seen from Table 4, compared with samples B1 and B2, the surface temperatures of samples R1c to R4c are significantly reduced, and the safety when the internal short circuit of the battery occurs can be further improved.

[0250] 《Samples R1d to R4d, Sample CRd》

[0251] The content ratio and average particle diameter (D50) of the polymer material (P) contained in the positive electrode mixture are changed as shown in Table 5. Except for this, samples R1d to R4d and CRd of the secondary battery are produced in the same manner as sample A1, and the evaluation is carried out in the same way.

[0252] [Table 5]

[0253]

[0254] In Table 5, compared with samples B1 and CRd, the surface temperatures of samples R1d to R4d are significantly reduced. From this, it can be known that the safety when the internal short circuit of the battery occurs can be improved.

[0255] 《Samples R1e to R4e, Sample CRe》

[0256] The content ratio of the polymer material (P) contained in the positive electrode mixture and the BET specific surface area were varied as shown in Table 6. Other than that, samples R1e to R4e and CRe of the secondary battery were fabricated in the same manner as sample A1, and evaluated in the same way.

[0257] [Table 6]

[0258]

[0259] In Table 6, the surface temperatures of samples R1e to R4e were significantly lower than those of samples B1 and CRe. Additionally, it was found that by reducing the BET specific surface area, the safety during internal short circuit of the battery could be improved.

[0260] 《Samples R1f to R3f, Sample CRf》

[0261] The content ratio of the polymer material (P) contained in the positive electrode mixture and the weight average molecular weight Mw were varied as shown in Table 7. Other than that, samples R1f to R3f and CRf of the secondary battery were fabricated in the same manner as sample A1, and evaluated in the same way.

[0262] [Table 7]

[0263]

[0264] In Table 7, the surface temperatures of samples R1f to R3f were significantly lower than those of samples B1 and CRf. Additionally, it was found that by reducing the weight average molecular weight Mw, the safety during internal short circuit of the battery could be improved.

[0265] 《Sample R1g》

[0266] The separator was changed to a separator having a microporous film substrate layer made of polyethylene with a thickness of 10 μm and a heat-resistant layer laminated on one side (positive electrode side) of the substrate layer. Other than that, sample R1g of the secondary battery was fabricated in the same manner as sample A1, and evaluated in the same way.

[0267] The melting point of the microporous film was 150 °C, and the melting point of PPS was 280 °C. The heat-resistant layer contained 20 mass% of an inorganic oxide filler (aluminum oxide), and the remaining part was composed of an aromatic polyamide, with a thickness of 4 μm.

[0268] 《Sample R2g》

[0269] The content ratio of the polymer material (P) contained in the positive electrode mixture was changed as shown in Table 8. Other than that, sample R2g of the secondary battery was fabricated in the same manner as sample R1g, and evaluated in the same way.

[0270] 《Samples CR1g, 2g》

[0271] The separator was changed to a microporous film of polyethylene without a heat-resistant layer and having a thickness of 13 μm. Except for this, samples CR1g and CR2g of secondary batteries were fabricated in the same manner as samples R1g and 2g, and evaluated in the same manner.

[0272] 《Sample CR3g》

[0273] A sample CR3g of a secondary battery was fabricated in the same manner as sample CR1g, except that the positive electrode mixture did not contain the polymer material (P).

[0274] [Table 8]

[0275]

[0276] Industrial Applicability

[0277] The non-aqueous electrolyte secondary battery of the present invention is useful as a main power source for mobile communication devices, portable electronic devices, electric vehicles, and the like.

[0278] Although the present invention has been described with respect to the presently preferred embodiments, such disclosure should not be construed in a limiting sense. Various modifications and changes will be apparent to those skilled in the art in the technical field to which the present invention pertains upon reading the above disclosure. Accordingly, the appended claims should be construed to cover all modifications and changes without departing from the true spirit and scope of the present invention.

[0279] Description of Reference Numerals

[0280] 10: Secondary battery, 11: Sealing body, 12: Valve body, 13: Metal plate, 14: Insulating member, 15: Positive electrode plate, 15a: Positive electrode lead, 16: Negative electrode plate, 16a: Negative electrode lead, 17: Separator, 18: Electrode group, 21: Gasket, 22: Battery can, 22a: Groove portion, 23: First insulating plate, 24: Second insulating plate

Claims

1. A non-aqueous electrolyte secondary battery includes a positive electrode, a negative electrode, a non-aqueous electrolyte, and a separator interposed between the positive electrode and the negative electrode. The positive electrode includes a positive electrode current collector and a positive electrode active material layer supported on the positive electrode current collector. The positive electrode active material layer contains a positive electrode active material, a binder, and an additive. The additive is a polymer material having a melting point or thermal decomposition temperature of 200 °C or higher and 500 °C or lower. In a cross-section of the positive electrode active material layer, the polymer material forms a plurality of island-like regions and is dispersed. The variance value of the Voronoi diagram when the cross-section of the positive electrode active material layer is subjected to Voronoi division for the island regions is 2×10 7 μm 4 or less.

2. The non-aqueous electrolyte secondary battery according to claim 1, wherein, The average perimeter of the island-like regions is 60 μm or less.

3. The non-aqueous electrolyte secondary battery according to claim 1, wherein, The average area of the island-shaped region is 200 μm 2 or less.

4. The non-aqueous electrolyte secondary battery according to claim 1, wherein, The average area of the top 3 of the said island-shaped regions with the largest areas is 900 μm 2 as follows.

5. The non-aqueous electrolyte secondary battery according to claim 1, wherein, The average particle size of the polymer material is 50 μm or less.

6. The non-aqueous electrolyte secondary battery according to claim 1, wherein, The BET specific surface area of the polymer material is 10 m 2 / g or less.

7. The non-aqueous electrolyte secondary battery according to claim 1, wherein, The weight average molecular weight Mw of the polymer material satisfies Mw < 50000.

8. The non-aqueous electrolyte secondary battery according to claim 1, wherein, The polymer material has a main chain containing a phenylene group and a thioether group.

9. The non-aqueous electrolyte secondary battery according to claim 8, wherein, The main chain contains a repeating structure represented by the following formula: n is an arbitrary integer.

10. The non-aqueous electrolyte secondary battery according to claim 9, wherein, The polymer material contains polyphenylene sulfide (polyphenylene sulfide).

11. The non-aqueous electrolyte secondary battery according to claim 1, wherein, The polymer material contains 10 ppm or more and 1000 ppm or less of chloride ions by mass ratio.

12. The non-aqueous electrolyte secondary battery according to claim 1, wherein, The content rate of the polymer material contained in the positive electrode active material layer is 0.01% by mass or more and 5% by mass or less.

13. The non-aqueous electrolyte secondary battery according to claim 1, wherein, When the thickness of the positive electrode active material layer is set to T, the presence probability Pb of the polymer material present in the region of the positive electrode active material layer from the surface of the positive electrode current collector to 0.5T and the presence probability Pt of the polymer material present in the region of the positive electrode active material layer from the position 0.5T away from the surface of the positive electrode current collector to the outermost surface satisfy 1 < Pt / Pb.

14. The non-aqueous electrolyte secondary battery according to claim 1, wherein, When the thickness of the positive electrode active material layer is set to T, the presence probability Pb of the polymer material present in the region of the positive electrode active material layer from the surface of the positive electrode current collector to 0.5T and the presence probability Pt of the polymer material present in the region of the positive electrode active material layer from the position 0.5T away from the surface of the positive electrode current collector to the outermost surface satisfy 1 < Pb / Pt.

15. The non-aqueous electrolyte secondary battery according to claim 1, wherein, The separator has a base material layer and a heat-resistant layer laminated on the base material layer. The melting point or thermal decomposition temperature of the polymer material is equal to or higher than the melting point of the base material layer.

16. The non-aqueous electrolyte secondary battery according to claim 1, wherein, The positive electrode active material contains a lithium-containing transition metal oxide. The lithium-containing transition metal oxide contains a lithium nickel oxide, and the lithium nickel oxide contains lithium and Ni and has a layered rock salt-type crystal structure. The proportion of Ni contained in the lithium nickel oxide among the metal elements other than Li is 50 atomic% or more.

17. The non-aqueous electrolyte secondary battery according to claim 16, wherein, The lithium nickel oxide is represented by the formula: Li α Ni x1 M1 x2 M2 (1-x1-x2) O 2+β as shown. Element M1 is at least one selected from the group consisting of V, Co, and Mn. Element M2 is at least one selected from the group consisting of Mg, Al, Ca, Ti, Cu, Zn, and Nb. And it satisfies: 0.95≤α≤1.05、 -0.05≤β≤0.05、 0.5≤x1<1、 0≤x2≤0.5、 0 < 1 - x1 - x2 ≤ 0.

5.

18. The non-aqueous electrolyte secondary battery according to claim 1, wherein, The binder contains at least one selected from the group consisting of a fluororesin and a hydrogenated nitrile rubber.

19. A positive electrode for a secondary battery, wherein the positive electrode active material layer contains a positive electrode active material, a binder, and an additive. The additive is a polymer material having a melting point or thermal decomposition temperature of more than 200°C and less than 500°C. In the cross-section of the positive electrode active material layer, the polymer material forms a plurality of island-shaped regions and is dispersed. The variance value of the Voronoi diagram when the cross-section of the positive electrode active material layer is subjected to Voronoi division for the island regions is 2×10 7 μm 4 or less.

Citation Information

Patent Citations

  • Positive electrode active material and lithium secondary battery using it

    JP2000315502A